KELAYAKAN PERLUASAN AREAL KEBUN KELAPA SAWIT 1000 HEKTAR (PENANAMAN BARU) DI PT BIO NUSANTARA TEKNOLOGI - Mulyasari, Gita; Wildayana, Elisa; Yamin, M. (Jurnal AGRISEP, 2006)
The purpose of this research are 1) to analyze TBS marketing aspect in Bengkulu Province that inflence by TBS accept and Demand. 2) to analyze technical aspect of 1.000 hectare palm oil plantation enlargement. 3) to analyze financial aspect of 1.000 hectare palm oil plantation enlargement. The research in PT. Bio Nusantara Teknologi used case method and supported by literatures study. he result of this research show that TBS marketing aspect in Bengkulu Province promised enough which increases TBS production. Technical aspect show enlargement of 1.000 hectare palm oil plantation is proper to do. From financial aspect with 18 % discount factor show gross B/C 1,65, NPV Rp. 18.574.764.528 and IRR 19,06 %, is proper to do.